Proses Pengolahan Terasi Udang Rebon Skala Rumah Tangga di Pesisir Pantai Lampu Satu Kabupaten Merauke - Sajriawati, Sajriawati (Nekton, 2022)
One of the catches of fishermen in the Marine Coastal of Lampu Satu is rebon shrimp, but the selling price is low and the durability is short so it quickly declines in quality (damaged). One effort to overcome this is by diversifying rebon shrimp products into shrimp paste so that the selling price goes up and the durability is long. The purpose of the study was to find out how the stages of the shrimp paste processing process. The research was carried out from November to December 2021 at the Marine Coastal of Lampu Satu, Merauke Regency. Research respondents are 1 group of household shrimp paste processors. The results showed that the shrimp paste processing process consisted of 10 stages of manufacture, namely sorting, washing, fermentation, drying stage 1, grinding stage 1, drying stage 2, grinding stage 2, printing, drying stage 3, and packaging. The processing of shrimp paste is still categorized as simple because everything uses a manual system of human power.